2016
DOI: 10.1371/journal.pone.0148177
|View full text |Cite
|
Sign up to set email alerts
|

Association Study of a Functional Variant on ABCG2 Gene with Sunitinib-Induced Severe Adverse Drug Reaction

Abstract: Sunitinib is a tyrosine kinase inhibitor and used as the first-line treatment for advanced renal cell carcinoma (RCC). Nevertheless, inter-individual variability of drug’s toxicity was often observed among patients who received sunitinib treatment. This study is to investigate the association of a functional germline variant on ABCG2 that affects the pharmacokinetics of sunitinib with sunitinib-induced toxicity of RCC patients in the Japanese population. A total of 219 RCC patients were recruited to this pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 27 publications
0
35
1
Order By: Relevance
“…Expression of the BCRP protein was reported to be 30-40% that of protein with the reference sequence, and expression in the placenta, specifically, also was reportedly lower [74,75]. The c.421C>A variant has been found to affect pharmacokinetics of, response to, and toxicity of compounds that are BCRP substrates, including chemotherapeutics and endogenous compounds [70,7881]. This variant was identified by the International Transporter Consortium as a clinically important transporter pharmacogene based on three criteria: 1) genome wide significance of an association between the variant and one or more drugs from genome wide association studies, 2) significant association of the variant and drug outcome from candidate gene studies, and 3) functional changes resulting from the polymorphism found in in vitro studies [4].…”
Section: Abcg2 Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the BCRP protein was reported to be 30-40% that of protein with the reference sequence, and expression in the placenta, specifically, also was reportedly lower [74,75]. The c.421C>A variant has been found to affect pharmacokinetics of, response to, and toxicity of compounds that are BCRP substrates, including chemotherapeutics and endogenous compounds [70,7881]. This variant was identified by the International Transporter Consortium as a clinically important transporter pharmacogene based on three criteria: 1) genome wide significance of an association between the variant and one or more drugs from genome wide association studies, 2) significant association of the variant and drug outcome from candidate gene studies, and 3) functional changes resulting from the polymorphism found in in vitro studies [4].…”
Section: Abcg2 Variantsmentioning
confidence: 99%
“…A study in people of Japanese descent reported a 1.9 - 3.5 times greater AUC of sulfasalazine in patients with the c.421C>A variant, but this finding was not replicated in a study of people of Chinese descent [83]. Other studies found that patients of Japanese descent with the c.421C>A variant who were being treated with sunitinib for advanced renal cell carcinoma were more likely to develop grade 3 or grade 4 thrombocytopenia [81,84,85], and that the variant was significantly associated with increased sunitinib exposure [86]. Furthermore, patients homozygous for the reference allele may have lower plasma concentrations of atorvastatin, simvastatin, and fluvastatin [1,87,88] and may respond more poorly to FOLFOX/XELOX therapy [89] compared to patients homozygous for the A allele.…”
Section: Abcg2 Variantsmentioning
confidence: 99%
“…Mizuno et al stated that the blood concentration of sunitinib is associated with polymorphism of the ATP binding cassette subfamily G member 2 (ABCG2) 421C>A 6. This genetic variant is significantly related to severe thrombocytopaenia following sunitinib treatment and is more frequently observed in Asian populations, including Japanese individuals, compared with in non-Asians 7. In this case, the severe adverse events and dramatic effect of treatment may be attributable to genetic susceptibility to TKI and overexposure to sunitinib, although the blood concentration of sunitinib was not confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to pathway analysis, presenters also described candidate gene analysis. For example, one investigator described a candidate gene study to test the hypothesis that sunitinib-induced thrombocytopenia is associated with a common reduced function variant (Q141K) in the transporter, ABCG2 (BCRP) 2 . Notably, the incidence of sunitinib-induced thrombocytopenia is higher in Asian populations, potentially due to a higher allele frequency of Q141K in Asians.…”
Section: New Discoveries In Cancer Pharmacogenomics (Liu Kroetz Innmentioning
confidence: 99%